(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article discusses the importance of learning foreign languages in human life. In today’s fast-paced world, knowing a foreign language is extremely important, because every sphere of life, business, education relies on a foreign language.